Characterization and Identification of Lactic Acid Bacteria (LAB) in Spontanoiusly Fermented Arabika (Coffea arabica L.) Fruits on Lombok Island - Muspiah, Aida; Nurrijawati, Nurrijawati; Julisaniah, Nur Indah; Farista, Baiq (Jurnal Biologi Tropis, 2025)
The quality of arabica coffee (Coffea arabica, L) is not only influenced by the quality of the coffee beans, but also by the distinctive flavor that is the main attraction for coffee lovers. Various coffee post-harvest processing methods have been developed, including fermentation. The presence of lactic acid bacteria (LAB) that important in the spontaneous fermentation, cause it can be influenced by the geographical location of arabica coffee plants. Currently, information on the presence of LAB in arabica coffee on Lombok Island has not been available. Therefore, it is important to identify the LAB involved in the spontaneous fermentation of Arabica coffee. This study aims to identify the species of LAB in arabica coffee on Lombok Island by the spontaneous fermentation method. Characterization and identification of bacteria were carried out using phenotypic identification and profile matching methods, which include several observation parameters, colony morphology and cell morphology, physiological tests (bacterial growth at certain pH and temperature), and biochemical tests such as catalase test and carbon source usage. In this study, nine pure isolates that belong to the LAB group were successfully isolated. Based on the identification results, LAB belonged to the genus Lactobacillus. The isolates identified consisted of one isolate of Lactobacillus plantarum (IBK1), one isolate of Lactobacillus sakei (IBK3), and seven other isolates identified as Lactobacillus sp (IBK2, IBK4, IBK5, IBK6, IBK7, IBK8, IBK9). These findings can be the first step in the development of starter cultures for controlled fermentation in Arabica coffee.